Permanence and Global Attractivity of a Discrete Logistic Model with Impulses. (5th September 2013) - Gao, Chunyu; Guo, Qingxi
Abstract : By piecewise Euler method, we construct a discrete logistic equation with impulses. The constructed model is more easily implemented at computer and is a better analogue of the continuous-time dynamic system. The dynamic behaviors of the constructed model are investigated. Sufficient conditions which guarantee the permanence and the global attractivity of positive solutions of the model are obtained. Numerical simulations show the feasibility of the main results.